Analysis of Meis2 knockout mice reveals Sonic hedgehog‐mediated patterning of the cochlear duct - Koo, Hei Yeun; Oh, Jae Hwan; Durán Alonso, María Beatriz; Hernández, Iris López; González‐Vallinas, Margarita; Alonso, María Teresa; Tena, Juan J.; Gil‐Gálvez, Alejandro; Giraldez, Fernando; Bok, Jinwoong; Schimmang, Thomas (Developmental dynamics, 2025)
Background The mechanisms underlying the formation of complex structures such as during the outgrowth of the cochlear duct are still poorly understood. Results We have analyzed the morphological and molecular changes associated with cochlear development in mouse mutants for the transcription factor Meis2, which show defective coiling of the cochlea. These morphological abnormalities were accompanied by the formation of ectopic and extra rows of sensory hair cells. Gene profiling of otic vesicles from Meis2 mutants revealed a dysregulation of genes that are potentially involved in Sonic hedgehog (Shh)‐mediated patterning of the cochlear duct. Like in Shh mutants, Meis2 defective mice showed a loss of genes that are expressed in the apical part of the cochlear duct. Conclusions Taken together, these data reveal that the loss of Meis2 leads to a phenotype that resembles Shh mutants, suggesting that Meis2 is instrumental for cochlear Shh signaling. The modulation of the same subset of genes provides an interesting insight into which Shh responsive genes are essential for outgrowth and patterning of the cochlear duct. Key Findings Loss of Meis2 leads to abnormal coiling of the cochlea and ectopic hair cells. Analysis of the transcriptome of Meis mutant otic vesicles reveals dysregulation of Sonic hedgehog target genes. Loss of apical gene expression in the cochlear duct resembles the phenotype in Sonic hedgehog mutants. Comparison between Meis2‐ and Sonic hedgehog‐target genes provides insights in which genes are required for proper patterning of the cochlear duct.